Angiogenesis in rheumatoid arthritis: epidemiology, pathogenesis, signal transduction pathways, and nano-targeted therapeutic strategies - Joan Blin; Mohd Rohaizad Md Roduan; Roslida Abd Hamid (Faculty of Medicine, Universitas Trisakti, 2025)
Angiogenesis is the formation of new blood vessels from existing vessels. In rheumatoid arthritis (RA), new blood vessels maintain a chronic inflammatory state by transporting inflammatory cells to the site of inflammation. Rheumatoid arthritis is a chronic autoimmune disorder that affects approximately 1% of the global population, with a higher prevalence in women. It is characterized by synovial inflammation, hyperplasia, and angiogenesis, leading to joint destruction. Understanding the pathogenesis of RA, particularly the mechanisms driving synovial angiogenesis, is crucial for the development of targeted therapies. Fibroblast-like synoviocytes (FLS) and endothelial cells play key roles in RA pathogenesis by secreting pro-inflammatory cytokines and growth factors, such as tumor necrosis factor (TNF)-alpha, interleukin (IL)-1β, IL-6, and vascular endothelial growth factor (VEGF). These mediators activate multiple signaling pathways, including VEGF, nuclear factor kappa light chain enhancer of activated B cells (NF-κB), phosphatidylinositol-3 kinase (PI3K)/AKT, mitogen-activated protein kinase (MAPK), wingless-related integration site (Wnt), and the Janus kinase (JAK)/ signal transducer and activator of transcription (STAT), which contribute to synovial angiogenesis, inflammation, and joint damage. A literature search was conducted on PubMed, ScienceDirect, SpringerLink, and Google Scholar databases for sources published in English from 2015 to 2025, using the terms “nanotechnology rheumatoid arthritis,” “angiogenesis,” “synovial inflammation,” “pro-inflammatory cytokines,” “disease-modifying antirheumatic drugs,” and “signal transduction pathways”. Current treatments for RA include nonsteroidal anti-inflammatory drugs (NSAIDs), glucocorticoids, and disease-modifying antirheumatic drugs (DMARDs) (conventional synthetic, biological, and targeted synthetic). An informative overview of anti-angiogenic strategies for treating RA, which may provide new perspectives for developing nanoagents, is opening new horizons in the fight against RA. This review covers RA epidemiology, pathogenesis, and signal transduction, as well as current therapies and their limitations, highlighting the need to develop new treatment strategies that target angiogenesis in RA.